A Narrative Review of Natural History of Diseases and Continuity of Care in Family Medicine - Jose L Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
Natural history of disease refers to the progression of a disease process in an individual over time. Family medicine has important epidemiological connotations, presenting a unique opportunity to study natural history of a disease. We present an example case of the natural history of the disease: the continued care of a patient with thromboangiitis obliterans for 37 years, who was continuously attended over many years in family medicine level, with the aim of refl ecting and conceptualizing the importance that, for epidemiological knowledge of natural history of diseases have the data provide by family medicine, which can be classifi ed as biopsychosocial typologies of the natural history of diseases, according to their pattern of natural history, and through an epidemiological classifi cation directed by medical intervention. So, there are two complementary perspectives to characterize the natural history of the disease: that of the general practitioner, who through the medical records the entire process of each patient, and can determine both that there is a new health problem and its peculiarities; is an individualized vision. And the epidemiologist, who through the multiple health records he handles, and the support of biostatistics can discover a new disease and its evolution; is a population view. Future epidemiological strategies that use longitudinal study designs or "continuing care", using homogeneous defi nitions of diseases, could play a pivotal role in better elucidating the controversies in natural history and the pathophysiology of subtypes of many common diseases, leading to improved clinical care. Cohort studies on the natural history of diseases should be enhanced in order to provide a basis for the development of health strategies and prevention and treatment measures. The ordinary general practitioners can make a signifi cant  contribution to research on the basis of patients seen in routine practice.